IMPLEMENTASI KONVENSI HAK-HAK PENYANDANG DISABILITAS TERKAIT AKSESIBILITAS PEKERJAAN DI KOTA PALU - Kennedi, Kaisha Adana; Takwa, Tuah Kalti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The Convention on the Rights of Persons with Disabilities (UNCRPD) is one of the international conventions that regulates the rights of persons with disabilities and has been adopted by ratifying countries. Indonesia, as one of the ratifying countries, has established national regulations through Law No. 8/2016 related to Persons with Disabilities. As a concrete step of implementation, local governments such as Palu City passed Local Regulation No. 10 of 2023 to affirm the commitment of local governments in ensuring the fulfilment of the rights of persons with disabilities, especially related to employment accessibility. This research analyses the implementation of UNCRPD in the initial policy of Palu City through the regulation during 2023-2024. This research analyzes how the implementation of UNCRPD in the initial policy of Palu City through the Local Regulation during 2023-2024. The analysis was conducted using a qualitative method by collecting primary data through interviews with relevant parties and secondary data through literature and document studies. This research uses constructivism perspective and Martha Finnemore and Kathryn Sikkink's norm internalization theory. The result of this research shows that the implementation of UNCRPD in Palu City has shown a progressive first step, but has not been fully achieved substantively. Thus, a more systemic and participatory approach is needed to encourage the effective implementation of the local regulation. Keywords: UNCRPD, Persons with Disabilities, Employment Accessibility